Condition monitoring of low voltage substations utilizing infrared thermography / Sarabi Mat Hassan - Mat Hassan, Sarabi (2001)
This report describes the condition monitoring (CM) of Low Voltage Substations utilizing Infrared Thermography (IR). Deep discussion will be concentrated on CM concept, thermography concept and the use of thermography inspection in helping Tenaga Nasional Berhad (TNB) related to breakdown, overload and tripping problems at substations. The equipment's inspected are transformers, low voltage board, substation components and transformer. A recommendation can be made so that proper action can be taken before the unit suffers additional damage. The developed software have been also developed to simulate of IR Analysis